'Clinical Legal Education'— Observing, Comparing and Analyzing the Differences in Germany and China for each other's Respective Advantages. (July 2015) - Hannemann, Jan-Gero Alexander; Lampe, Jan Hendrik
'Clinical Legal Education' in Germany and China is a new approach towards changing (one might even say completing) law studies and the curriculum at universities. It provides a lot of opportunities and benefits for the participating students and thereby for the broader community. Adapted from US legal clinics, clinical legal education has changed within the last few years both legal systems and legal education. The surprisingly strong development in Germany and China which could not be more different shows many interesting aspects on how to build up legal clinics and how to influence the society within. In both countries education used to be dominated by theory. Practical matters were not, or at least not for students taken into consideration for a sufficient amount of time. The authors attempt to compare and analyze the development of clinical legal education and student legal services in China and Germany. This analysis provides a broad approach from the historical roots to the development and thereby influence of the national umbrella organizations and cross-border influences. One does not only find many similarities, but also discovers a common understanding of legal clinical education as well as differences that can be used to understand one's own legal clinic system and develop it further. This analysis provides the possibility to strengthen the global development of 'clinical legal education'.